Analysis of Mathematics Literacy Ability Based on Problem Solving Ability For Class VII Students of SMP Bunda Rangkiang - Meiningrum, Niken; Wahidin, Wahidin (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
In modern times, students are required to have logical, creative, and critical thinking in order to be able to manage and deal with problems that exist in real life. This study aims to analyze mathematical literacy based on the problem-solving abilities of students. The type of research used is qualitative research with a case study research method. The subjects in this study were 9 students of grade VII SMP Bunda Rangkiang. The results of this study are descriptive related to mathematical literacy, among others, to formulate, apply, and interpret using PISA (Program for International Students Assessment) questions. It can be seen from the mathematical literacy of students in the low category 42.85%, the medium category 75%, and the high category 89.28%.